PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING (PjBL) TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA KELAS X MA MU’ALLIMAT NWDI PANCOR - Milasari; M. Khairul Wazni; Wawn Muliawan; Nunung Ariandani (UNIVERSITAS HAMZANWADI, 2024)
This study aims to determine the effect of the Project Based Learning (PjBL) learning model on students' creative thinking skills on environmental pollution material. This type of research uses Quasi Experimental Design. The population of this study were all grade X students at MA Mu'allimat NWDI Pancor. The sample of this study was determined by Simple Random Sampling technique. Class X B as an experimental class using the Project Based Learning (PjBL) model and class X A as a control class using the lecture method. The research design used is Posttest-Only Control design which has been modified on the posttest value which is not obtained from student test scores after learning, but student creative thinking after learning. Data collection techniques used documentation, LKPD, and flower vase creativity assessment sheets. Data were analyzed using independent t-test analysis. The hypothesis results show that tcount> ttable, namely (2.795> 1.161) which means H0 is rejected and Ha is accepted, so it can be concluded that there is an effect of the Project Based Learning (PjBL) learning model on the Creative Thinking Ability of Class X MA Mu'allimat NWDI Pancor Students.